Librarian involvement on knowledge synthesis articles and its relationship to citation counts and Journal Impact Factor - Krista Alexander; Katharine Hall; Yuling Max Chen (Journal of the Canadian Health Libraries Association)
Introduction: Our aim was to determine if there is a relationship between librarian involvement on a knowledge synthesis project and the synthesis’s citation count or the Journal Impact Factor (JIF) of its publication venue.